ANALISIS KELENGKAPAN MATERI BUKU TEKS SEJARAH KELAS XI YANG DIPAKAI DI SEKOLAH-SEKOLAH SMA DI KOTA PADANG (BUKU ERLANGGA, PLATINUM, BUMI AKSARA, DAN YUDISTRIRA) (Jurnal Pelangi : Research of Education and Development, 2015)
Textbook is the handbook used by teachers in teaching. In addition, the text book is also used by students as a supporting book in learning activities both in school and outside of school. Textbooks basically have a very important role for teachers and students in the learning process. But in reality, many textbooks are found that do not meet the requirements of many textbooks used in the Senior High School Level.  The researchers took several textbooks compared to the completeness of the material. This research examines the differences of the structure and content of the description text book material of the History learning of Senior High school class X in the process picture changes, facts, concepts and principles in the history of motion. The type of research was a library research, collection techniques and conducting a review of the study of books, literature, records and reports that are related to the problem being solved. Data were taken from the existing instruments in the history textbooks. The results show that the components of change in motion events based on facts concepts and principles includes four components, namely changes in the beginning, development, backward and finished. Completeness of the materials at the eleventh grade history textbook in this research material examined the influence of religion and Hindu-Buddhist culture in Indonesia and the influence of the religion and culture of Islam in Indonesia. From the analysis, it is shown that each textbook has some differences in the completeness of the material on Hindu and Buddhist kingdoms. The book outlines eight royal grants, Yudhisthira, Earth Literacy and Platinum each of the seven kingdoms. While the analysis for the development of each book has its advantages and disadvantages, there is a book which describes the initial process completely and there is not. To evolve from the four aspects of political, social, economic and cultural, one book with another book also has its advantages and disadvantages, so that the backward and end process.